Kommunikasie met pasiënte - Die effek van verbale en nie-verbale kommunikasie op bewustelose pasiënte - M. Weich (AOSIS, 1992)
Communication, both verbal and non-verbal, is a greatly neglected Skill at present. Two reasons given for this state of affairs are lack of time and lack of interest in others. Since it is difficult to separate verbal and non-verbal communication, the effects of both types were studied, whether or not they occurred simultaneously. Empirical evidence shows that unconscious patients are highly sensitive to the nature of communication, and that their intracranial pressures rise or fall concomitant in the way in which a conversation is being conducted within hearing distance. Music and touch seem to have similar consequences. The influence of communication is, however, not confined to intracranial pressure changes. The sympathetic and parasympathetic nervous systems are also affected, with associating changes in the heart rate. Messages of acceptance or rejection may be conveyed verbally or non-verbally. Communication with patients appears to be decisive, and should therefore warrant far greater attention than it receives at present.